PENDEKATAN HUMANISTIK DALAM MENINGKATKAN DISIPLIN SALAT DUHA DI SD ISLAMIC GREEN SCHOOL SALATIGA - Multazam, Umar; Rahmawati, Lutfia (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2024)
This study aims to analyze the obstacles in the implementation of the humanistic approach to improve the discipline of dhuha prayer at SD Islamic Green School Salatiga. The humanistic approach conveys the holistic needs of students, including physiological aspects, security, love and belonging, self-esteem, and self-actualization. In this context, the humanistic approach, This study uses a qualitative method with a descriptive approach. Data collection techniques used include observation to collect information and data related to the implementation of discipline in performing dhuha prayer through humanistic theory, interviews with parties directly involved such as the principal, vice principal, and teachers who accompany students of SD Islamic Green School Salatiga, and documentation to obtain data on student discipline in performing dhuha prayer at SD Islamic Green School Salatiga. Triangulation was employed by the researcher using cooperative techniques of documenting, interviewing, and observation that support one another. According to the study's findings, the idea of humanistic learning theory is understood as optimizing the process of physical and spiritual development, which encompasses the needs for self-actualization or personal growth, security, love, and belonging, as well as physiological or biological needs. Making an agreement with the school community, asking students questions, and playing visually appealing movies are the first steps in enforcing student discipline when conducting the Dhuha prayer.. Obstacles in the humanistic theory approach at SD Islamic Green School Salatiga include low motivation, poor time management, educators who are inconsistent in providing reinforcement, and students who do not yet have an awareness of the importance of discipline. Keywords: Humanistic, Discipline, Personal Development, Dhuha Prayer.